PENGARUH KUALITAS AUDIT DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Himawan, Chealsea Aury; Suryanto, Suryanto (E-Jurnal Akuntansi TSM, 2024)
Abstract: The purpose of this study is to empirically examine the factors that affect the earnings management. This study uses independent variables audit quality, financial leverage, profitability, firm size, sales growth, audit committee, free cashflow, company age and earnings management as the dependent variable. The study was conducted on 61 consumer cyclicals & consumer non-cyclicals companies listed on the Indonesia Stock Exchange from 2020 to 2022 which were obtained using purposive sampling method. Samples and data were tested and analyzed using multiple regression methods. The results of this study indicate that audit quality and free cashflow have a negative effect and profitability has a positive effect on earnings management. While financial leverage, firm size, sales growth, audit committee, and company age have no effect on earnings management coefficient.